The Role of the United States and The â€œAsian Solutionâ€ Approach in the Malaysia-Indonesia Confrontation (1963-1966) (Journal of International Studies, 2020)
The Indonesia-Malaysia confrontation between 1963-1966 was an important event attracting the attention of politicians and scholars alike as the conflict had threatened the long existing relations between the two countries. Indonesian confrontation with Malaysia was due to its refusal to accept the formation of the new federation of Malaysia, founded on 16th September 1963. Sukarnoâ€™s confrontational stand on this had broken the long-standing sentiments of regional brotherhood or â€œsaudara serumpunâ€ that had nurtured between the two countries for many years. The conflict also saw the involvement of major powers like the United States (U.S.), Britain, China and Russia in the midst of bipolar power struggle between the communist and the anti-communist as part of the ongoing Cold War. The three years of confrontation witnessed great attempts at peace efforts by U.S. Although U.S. involvement in the conflict was merely as a moderator for both countries it was also fueled by its efforts of containment of communism in the Southeast Asian region. The U.S. viewed that the conflict should be resolved in the context of â€œAsian solutionâ€ as it involved two Asian countries A settlement to the Malaysia-Indonesia confrontation was finally achieved through the Bangkok Agreement, signed in August 1966. This paper discusses the role of U.S. in its attempts at finding an amicable settle to the confrontation in the form of â€œAsian solution.â€